The bees of the genus Hylaeus Fabricius, 1793 of Turkey, with keys to the subgenera and species (Hymenoptera: Anthophila, Colletidae) - Özbek , Hikmet; Dathe, Holger H. (Contributions to Entomology = Beiträge zur Entomologie, 2020)
The paper presents data of around 4000 previously unpublished specimens, collected in various parts of the country during the last decades. With literature sources, a total of 86 species of the genus Hylaeus Fabricius, 1793 from 10 subgenera are compiled for Turkey. New for Turkey are 11 species: Hylaeus (Dentigera) kahri Förster, 1871, H. (Dentigera) pallidicornis Morawitz, 1876, H. (Hylaeus) deceptorius (Benoist, 1959), H. (Hylaeus) gracilicornis (Morawitz, 1867), H. (Hylaeus) paulus Bridwell, 1919, H. (Hylaeus) trisignatus Morawitz, 1876, H. (Nesoprosopis) pectoralis Förster, 1871, H. (Prosopis) incongruus Förster, 1871, H. (Prosopis) trinotatus (Pérez, 1896), H. (Prosopis) variolaris Morawitz, 1876 and H. (Spatulariella) sulphuripes (Gribodo, 1894). No new specimens could be found of 13 species which had been detected formerly. Our knowledge on the distribution of numerous species is greatly expanded. The characteristics of distribution are defined for the individual species. For example, H. meridionalis is the most widespread with records from 46 provinces covering all geographical regions of the country, while many other species are only known from one province, sometimes from a single record. The eastern part of Turkey, in particular the province of Hakkâri, proved to be an important centre of diversity for Hylaeus species. For a number of species the valid names had to be revised. Distribution maps are presented for the newly recorded and rare species. Frequently visited plant species are mentioned. Keys to the subgenera and species of Turkish Hylaeus are provided. Nomenclatural acts All species described by Warncke in 1981 and 1992 from Turkey in the genus Prosopis F. have not yet been revised and formally combined with the valid genus name Hylaeus F. There are however a number of online checklists, which have already registered most of these names under Hylaeus. Representatives of these checklists were checked here: The World Bee Checklist, integrated into the ITIS database (ITIS 2020) and Discover Life (Ascher & Pickering 2019). As new combinations, only the missing names are added here. Hylaeus (Dentigera) giresunus (Warncke, 1992) – comb. et stat. nov. Hylaeus (Hylaeus) trochilus (Warncke, 1992) – comb. et stat. nov. Hylaeus (Paraprosopis) decaocto (Warncke, 1992) – comb. nov. Hylaeus (Paraprosopis) socheri Dathe, 2010 = H. (Paraprosopis) decaocto (Warncke, 1992) – syn. nov. Prosopis styriaca crecca Warncke, 1992 = Hylaeus (Paraprosopis) styriacus Förster, 1871 – stat. nov. Hylaeus (Spatulariella) planulus (Warncke, 1981) – comb. nov. Hylaeus (Spatulariella) tauricus Warncke, 1981 – comb. nov.